2014
DOI: 10.1111/ajsp.12078
|View full text |Cite
|
Sign up to set email alerts
|

Transmitting pro‐environmental behaviours to the next generation: A comparison between Germany and Japan

Abstract: The present study examined the processes by which children acquire pro-environmental behaviours in different cultures. Our focus was on parental influence. Several studies have been conducted on adults' environmental behaviours; however, we know little about how children's environmental attitudes and behaviours are formed. We conducted a questionnaire survey with elementary school children and one of their parents in Germany and Japan. Two hundred and twenty-one pairs participated in Germany and 365 in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 40 publications
9
55
0
12
Order By: Relevance
“…Thus, it can be discussed that respecting seniority in Thai norms derived high scores of the subjective norms. On the other hand, it was reported that it is more important to meet the expectations of others in interdependent cultures, and this normative factor, namely, the subjective norms play a vital role in determining the environmental behavior for children in Japan (Ando, Yorifuji, Ohnuma, Matthies, & Kanbara, 2015). This suggestion can support that the current study elucidated the parental influence on energy literacy of students in Japan by examining the presence of home discipline in energy-saving.…”
Section: Country Effect On Energy Literacy Modelsupporting
confidence: 72%
“…Thus, it can be discussed that respecting seniority in Thai norms derived high scores of the subjective norms. On the other hand, it was reported that it is more important to meet the expectations of others in interdependent cultures, and this normative factor, namely, the subjective norms play a vital role in determining the environmental behavior for children in Japan (Ando, Yorifuji, Ohnuma, Matthies, & Kanbara, 2015). This suggestion can support that the current study elucidated the parental influence on energy literacy of students in Japan by examining the presence of home discipline in energy-saving.…”
Section: Country Effect On Energy Literacy Modelsupporting
confidence: 72%
“…According to pro-environmental consumption theory, various socio-psychological constructs are proposed as important determinants of pro-environmental behaviour (Bamberg & Möser, 2007), such as demographics (e.g., Ando, Yorifuji, Ohnuma, Matthies, & Kanbara, 2015;Robinson & Smith, 2002), knowledge (e.g., Bartkus, Hartman, & Howell 1999;Pedersen & Neergaard, 2006), affect (e.g., Chan, 2001;Martin & Simintiras, 1995), attitudes (e.g., Dunlap, Van Liere, Mertig, & Jones, 2000;Wray-Lake, Flanagan, & Osgood, 2010), values (e.g., Chen, 2015;Fryxell & Lo, 2003 ), and lifestyles and habits (e.g., Lebel & Lorek, 2008;Welsch & Kühling, 2009). Nevertheless, the exact relationships of these various constructs with proenvironmental consumption behaviour are still unclear (Bamberg & Möser, 2007), particularly in Chinese cultural contexts.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Studi lainya juga menunjukkan bahwa perilaku orangtua yang ramah lingkungan mempengaruhi perilaku anak menjadi ramah lingkungan [9,10]. Ini juga dikuatkan oleh hasil studi Ando et al pada anak-anak di Jerman dan di Jepang bahwa perilaku ramah lingkungan oleh anak karena kegiatan sehari-hari di rumah [11]. Norma-norma dalam rumah yang diterapkan oleh orangtua yang mampu mempengaruhi anak lebih ramah lingkungan [12].…”
Section: Pendahuluanunclassified